Analisis Pengaruh Prinsip Pariwisata Halal Terhadap Peningkatan Pendapatan Usaha Mikro Kecil dan Menengah (UMKM) di Destinasi Wisata Taman Kota Kabupaten Mukomuko - Ahmad Rifa’i; Andang Sunarto; Rahmat Putra Hasibuan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
Halal tourism is one of the sectors that has experienced rapid development in recent years, along with the increasing awareness of Muslim communities regarding the importance of tourism services that comply with Islamic principles. This study employs an associative/causal research design, which aims to examine the relationship as well as the influence between two or more variables. In this research, the independent variables consist of muamalah (X1), worship/ibadah (X2), and morality/akhlak (X3), which are analyzed for their effects on the dependent variable, namely MSME income (Y).This study adopts a quantitative approach using multiple linear regression analysis. The results show that based on the partial test (t-test), the variables of muamalah, worship (ibadah), and morality (akhlak) each have a significant effect on MSME income. The muamalah variable has a t-value of -5.596 with a significance level of 0.000, the worship (ibadah) variable has a t-value of 4.955 with a significance level of 0.000, while the morality (akhlak) variable shows the most dominant influence with a t-value of 47.630 and a significance level of 0.000.